PENEGAKAN KODE ETIK NOTARIS TERHADAP LARANGAN PROMOSI MELALUI MEDIA ELEKTRONIK DI KOTA YOGYAKARTA - , AISYA RAISA ASTONISH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was intended to study enforcement of notary code of ethic (KEN) over prohibition of promotion through electronic media in Yogyakarta City and factors supporting and hampering the enforcement. It is juridical empirical research using primary and secondary data through library study with material including primary, secondary, and tertiary law material. Field research used non random sampling and sample was taken using purposive sampling. The research was conducted in Yogyakarta with subject of Yogyakarta INI chief, regional supervisory council (MPD) and chief of regional honorary committee (DKD). Secondary data used documentary method with documentary study instrument. Primary data was obtained through interview guide. Data was analyzed qualitatively. The result indicated that enforcement KEN over prohibition of promotion through electronic media in Yogjakarta has been no action firmly over the suggestion the violations KEN. DKD functions as patron, supervisor, and keep notary over KEN and/or organizational discipline in internal affair. MPD function as patron, supervisory, and improving notary in doing their position based on laws and KEN. Factors influencing KEN enforcement are: (1) Law factor